OP0092 Interleukin 37 reverses the metabolic cost of inflammation, increases oxidative respiration and improves exercise tolerance. (15th June 2017) - Cavalli, G; Ballak, D; Justice, JJ; Boyle, K; D'Alessandro, A; Joosten, LA; Dagna, L; Dinarello, CA
Abstract : Background: The IL-1 family cytokine interleukin 37 (IL-37) has broad anti-inflammatory effects and functions as a natural suppressor of innate inflammation and acquired immunity (1). We have reported that administration of recombinant human IL-37 to wild type mice or expression in mice transgenic for human IL-37 suppress proinflammatory cytokines and curb excessive inflammation in various conditions including inflammatory arthritis (2). Besides these anti-inflammatory effects, IL-37 also induces complex effects on metabolism. In particular, IL-37 can directly activate AMP-activated protein kinase (AMPK), a central regulator of cellular energy homeostasis and exercise-regulated metabolism (3). Objectives: In this study, we evaluate the effects of IL-37 treatment on exercise tolerance in mice with systemic inflammation induced by LPS injection. We further investigate the effects of IL-37 on exercise tolerance in healthy mice, with specific focus on the metabolic changes induced by IL-37 administration and possibly responsible for a reduction in the metabolic costs of inflammation. Results: Exogenous administration of IL-37 to healthy mice, not subjected to an inflammatory challenge, also improved exercise performance by 82% compared to vehicle-treated mice ( p =0.01). Treatment with 8 daily doses of IL-37 resulted in a further 326% increase in endurance running time compared to the performance level of mice receiving vehicle ( p =0.001). These properties required the engagement of the IL-1 decoy receptor 8 (IL-1R8) and the activation of AMP-activated protein kinase (AMPK), since both inhibition of AMPK and IL-1R8 deficiency abrogated the positive effects of IL-37 on exercise performance. Mechanistically, treatment with IL-37 induced marked metabolic changes with higher levels of muscle AMPK, greater rates of oxygen consumption and increased oxidative phosphorylation. Metabolomic analyses of plasma and muscles of mice treated with IL-37 revealed an increase in AMP/ATP ratio, reduced levels of pro-inflammatory mediator succinate and oxidative stress-related metabolites as well as changes in amino acid and purine metabolism. Conclusions: These effects of IL-37 to limit the metabolic costs of chronic inflammation and to foster exercise tolerance provide a rationale for therapeutic use of IL-37 in the treatment of inflammation-mediated fatigue. References: Dinarello CA, et al. (2016) Suppression of innate inflammation and immunity by interleukin-37. Eur J Immunol. Cavalli G, et al. (2016) Treating experimental arthritis with the innate immune inhibitor interleukin-37 reduces joint and systemic inflammation. Rheumatology (Oxford). Ballak DB, et al. (2014) IL-37 protects against obesity-induced inflammation and insulin resistance. Nature communications. Disclosure of Interest: None declared